Internalisasi Perilaku Keagamaan berbasis Wasathiyah dan Motivasi Belajar Siswa - Isnaeni Puji Lestari Lestari (IAIN PAREPARE, 2022)
Globalization poses various challenges, one of which is redusing deviant behavior that occurs everywhere, including students at the school level. To parent deviant behavior, it is necessary to inculcate religious behavior and motivation to learn in students. Wasathiyah-based religious behavior is able to change students’ personalitiesto be better individuals who an beat the current developments. The formation of wasathiyah-based religious behavior and learning motivation is carried out in daily habits. This research uses descriptive qualitative method. Data collaction techniquesusing interviews, observation, and documentation were analyzed descriptively. While the data analysis used is data reduction, data presentation, and verification or making conclusions. The validity of the data used two techniques, namely source triangulation and technical triangulation. The result of this study indicate that: the application of internalize of student wasathiyah-based religious behavior includes tolerance, congregational prayers, and infaq. The supporting and inhibiting factors for the internalization of wasathiyah-based religious behavior and student learning motivastion are seen from the guidance of parents and teachers and infrastructure.